Praxis der Digitalen Signalverarbeitung - Puente León, FernandoBauer, Sebastian (KIT Scientific Publishing, 2017)
The basics of digital signal processing are introduced with eight practical experiments. The experiments cover a wide range of different topics such as sensor fusion, vibration analysis, acoustics and image processing. The presented techniques aim at making the reader familiar with the practical application of modern methods of signal processing. The mastering of these helpful tools is often a requirement in daily professional life.